(untitled) (The International Journal for Scientific Research, 2026)
Amid rapid global administrative transformations, the application of Business Process Reengineering (BPR) has become an urgent necessity for government institutions to keep pace with developments and achieve competitiveness. This research aims to design a proposed model for BPR in the Iraqi Ministry of Youth and Sports to address Unjustified inflation of the organizational structure and modernize its organizational structures. Methodology: The research adopted a descriptive-analytical approach (case study and organizational design), relying on the researcher’s 15 years of field observation in the Ministry’s departments, in addition to analyzing periodic reports and institutional strategies in light of systems theory. Results: The analysis revealed that the current administrative systems suffer from bureaucracy and redundancy, weakening the effectiveness of its outputs. A proposed model based on a "flat management system" was developed, which included merging and eliminating certain departments (e.g., eliminating the Engineering Affairs Department) and creating new ones (such as the Talent Care Directorate and the Advisory Bureau) to enhance decentralization and speed up decision-making. Conclusions & Recommendations: The research recommends adopting the proposed model, shifting towards flat organizational structures, and conducting continuous periodic evaluations to ensure comprehensive quality.